Acridine modified dibenzothiophene derivatives as high triplet energy host materials for blue phosphorescent organic light-emitting diodes. (November 2015) - Kim, Ji Han; Hwang, Seok-Ho; Song, Wook; Lee, Jun Yeob
Abstract: Acridine modified dibenzothiophene derivatives were synthesized as host materials of imidazole ligand based Ir emitters for blue phosphorescent devices. The shallow energy levels of the acridine based host materials by the strong electron donating acridine moiety were well matched with the energy levels of Ir blue triplet emitter derived from imidazole. Additionally, strong electron transporting character of the acridine moiety could increase hole density in the emitting layer and balance holes and electrons. The energy level matching between the host and dopant materials and increased hole density in the emitting layer provided a very high external quantum efficiency of 27.8% in the blue phosphorescent organic light-emitting diodes. Highlights: Acridine and disbenzothiophene based high triplet energy host material. Hole transport type host material for imidazole based blue phosphorescent emitter. Improved lifetime and efficiency by combining dibenzothiophene and acrididine moieties in the host design.